Elucidating the Germanium Distribution in ITQ‐13 Zeolites by Density Functional Theory. Issue 14 (17th February 2022) - Fischer, Michael; Bornes, Carlos; Mafra, Luís; Rocha, João
Abstract: ITQ‐13 is a medium‐pore zeolite that can be prepared in all‐silica form and as silicogermanate with Si/Ge ratios as low as 3. Usually synthesised in the presence of fluoride, ITQ‐13 is among the very few systems containing fluoride anions in two distinct cage types, cube‐like d4r units and [4 ⋅ 5 6 ] cages. Here, dispersion‐corrected density functional theory (DFT) calculations are used to investigate the energetically most favourable Ge distributions for Si/Ge ratios between 55 and 6. The calculations show Ge atoms are incorporated at both the corners of d4r cages and at the basal plane of the [4 ⋅ 5 6 ] cages, in accordance with 19 F NMR spectroscopy. Two Ge atoms at adjacent corners of [4 ⋅ 5 6 ] cages are stable at the highest Ge content considered (Si/Ge=6). Such a local environment has not yet been considered in the experimental literature. A calculation of the corresponding 19 F NMR resonance points to overlap with other resonances, which might preclude its clear identification. Additional calculations investigate the variation of the dynamic behaviour of the fluoride anions as a function of the local environment as well as the selective defluorination of the [4 ⋅ 5 6 ] cages. Abstract : The preferred Ge distributions in ITQ‐13 silicogermanates with different Si/Ge ratios were investigated with electronic structure calculations, with the primary aim of predicting the most stable local structures across the range of Ge contents. Additional calculations were used to study the variation of the dynamic behaviour of the incorporated fluoride anions as a function of the local environment and the defluorination behaviour of different fluoride‐containing cages.